Challenges in Management of Tracheobronchial Foreign Bodies with Delayed Presentation: An Institutional Experience - Kaushal,Darwin (2022)
Abstract Introduction Airway foreign bodies are emergencies involving multidisciplinary departments like Pediatrics, Aneasthesiology and Otorhinolaryngology. It is always a challenge to diagnose and manage patients who present late to our emergencies. Objective In the present study, we aim to analyze the various challenges faced during the management of tracheobronchial foreign bodies with delayed presentation. Methods A retrospective hospital record-based analysis of patients who presented to us with tracheobronchial foreign bodies from January 2017 to February 2020 was performed. All patients until the age of 16 years old were included in the present study. We assessed the demographics, preoperative, intraoperative and postoperative data of the patients. Results Seventeen patients were analyzed in the study. Among these, 44.4% of the patients had delayed presentation (> 1 month). The majority of the patients had an organic foreign body (Supari or betel nut). All patients underwent rigid bronchoscopy, followed by optical forceps-assisted removal of the foreign body. A total of 82% of the patients had granulations around the foreign body. Conclusion Management of delayed presentation tracheobronchial foreign body is a big challenge for Otorhinolaryngologists. The key factors for preventing complications in the definitive management of tracheobronchial foreign bodies are preoperative planning, multi-discipline teamwork, surgeon expertise and technique.